Mathematical Modelling Ability in Outdoor Learning with Mobile Math Trails - Nugraha, Adam Arya; Rizal, Nur; Cahyono, Adi Nur (International Journal on Emerging Mathematics Education, 2023)
The aim of this study is to describe how outdoor learning with mobile math trails can support students' mathematical modelling ability. The method used is design research with three phases, namely preparation and design, teaching experiment, and retrospective analysis. This study was conducted at junior high school involving 32 students. The Hypothetical Learning Trajectory (HLT) was designed and learning activities that include several math trails tasks were created, then students run the activity. Data were collected by observation, interviews, tests, and worksheets. The findings indicate that the learning activity that has been implemented can support students’ mathematical modelling ability. The learning activity can provide opportunities for students to engage in meaningful mathematical modelling activities in accordance with mathematical modelling indicators. The study identified a link between HLT as learning design and mathematical modelling activities in learning process. In addition, it was found that students' mathematical modelling ability had improved.